An Evolutionary Analysis of Turnout with Conformist Citizens - LANDI, Massimiliano (Institutional Knowledge at Singapore Management University, 2012)
We propose an evolutionary analysis of a voting game where citizens have a preference for conformism that adds to the instrumental preference for the electoral outcome. Multiple equilibria arise, and some generate high turnout. Simulations of best response dynamics show that high turnout is asymptotically stable if conformism matters but its likelihood depends on the reference group for conformism: high turnout is more likely when voters care about their own group's choice, as this better overrides the free rider problem of voting games. Comparative statics on the voting cost distribution, the population's size or the groups' composition are also done.